Life in border regions: "Where would we end up?" - Annette Spellerberg; Antje Schönwald; Katharina Engelhardt; Florian Weber (Border Futures - Zukunft Grenze - Avenir Frontière: The future viability of cross-border cooperation, 2022)
What is life in a border region like? This paper aims to answer this question, drawing on empirical research in four twin villages in the Greater Region. The findings, based on a postal survey in the twin municipalities and face-to-face interviews, show that both sides see the border situation as bringing financial and practical advantages. The cooperation between the municipalities is generally described very positively. In regard to a sense of identification, there are feelings of belonging to both the nation state and the (cross-border) region, although there are differences between those surveyed in the different countries. In terms of the importance of the border, there is general agreement that it is scarcely noticed anymore, and that since its disappearance life has become more convenient and has benefited. Yet there various challenges can also be identified, which represent tasks for the coming years.
urn:nbn:de:0156-40971058; hdl:10419/258994; https://econpapers.repec.org/RePEc:zbw:arlabe:33
Keywords: 710; Border region; twin municipalities; cross-border cooperation; home; quantitative and qualitative research